Partymonster - Bailey, Fenton; Barbato, Randy; Maniaci, Teodoro; Culkin, Macaulay; Manson, Marilyn; Green, Seth; Sevigny, Chloë (Ascot Elite, 2005)
"Party Monster" is the true story of Club Kid Michael Alig and his rise and fall from NYC circuit party fame. Michael moved to the Big Apple from the Midwest to reinvigorate the defunct post-Studio 54 nightlife scene in the late '80s and early '90s. His trademarks were wild parties at Limelight, where people danced in gory blood-soaked dresses, often around a man in a chicken suit. He also held impromptu drug-fueled social gatherings at subway stations and in the back of 18-wheelers. The whole scene imploded when Michael killed a drug dealer, then bragged about it on television. The story dominated New York papers, became a best-selling novel by scene participant James St. James, and was the subject of a 1998 cable TV documentary called "Party Monster: The Shockumentary". In 2003, the makers of the documentary decided to make a theatrical film out of the same material, and thus "Party Monster" the movie was born. [www.dvdverdict.com]
Keywords: DVD-Video